2019
DOI: 10.1021/acs.joc.9b02733
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Catalyzed Transfer Hydrogenation in Aged N-Methyl-2-pyrrolidone: Reductive Ring-Opening of 3,5-Disubstituted Isoxazoles and Isoxazolines

Abstract: 3,5-Disubstituted isoxazoles and isoxazolines undergo an iron-catalyzed reductive ring-opening in aged N-methyl-2-pyrrolidone (NMP). 5-Hydroxy-N-methyl-2-pyrrolidone generated in situ via a simple activation of commercial NMP acts as the hydrogen donor in the iron-catalyzed transfer hydrogenation reaction. It is the first example employing a combination of an iron catalyst and 5-hydroxy-N-methyl-2-pyrrolidone as reducing agents in a transfer hydrogenation reaction. The protocol is highly efficient for the synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…2,3,5‐Trisubstituted pyrrole 2 a was obtained in 62% yield after 15 hours (Table , entry 1). Further experimental data revealed that the ring‐opening of 4‐alkenylisoxazole 1 a did not depend on the aged NMP solvent, unlike the previous iron‐catalyzed reductive ring‐opening of 3,5‐disubstituted isoxazole reaction or the ring‐opening of 4‐alkynylisoxazoles to polysubstituted furans . Substrate 1 a reacted smoothly in non‐activated NMP solvent and afforded the same rearrangement product 2 a in 68% yield (Table , entry 2).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…2,3,5‐Trisubstituted pyrrole 2 a was obtained in 62% yield after 15 hours (Table , entry 1). Further experimental data revealed that the ring‐opening of 4‐alkenylisoxazole 1 a did not depend on the aged NMP solvent, unlike the previous iron‐catalyzed reductive ring‐opening of 3,5‐disubstituted isoxazole reaction or the ring‐opening of 4‐alkynylisoxazoles to polysubstituted furans . Substrate 1 a reacted smoothly in non‐activated NMP solvent and afforded the same rearrangement product 2 a in 68% yield (Table , entry 2).…”
Section: Resultsmentioning
confidence: 85%
“…A series of 4‐alkenylisoxazoles 1 were synthesized by a palladium‐catalyzed cascade cyclization‐alkenylation protocol previously reported by our group . We chose ( E )‐3‐( tert ‐butyl)‐5‐phenyl‐4‐styrylisoxazole 1 a as the model substrate for reaction condition optimization, and first employed the conditions reported in our previous iron‐catalyzed reductive ring‐opening of 3,5‐disubstituted isoxazoles . To our delight, a ring‐opening and rearrangement cascade took place smoothly in the presence of 0.15 equiv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these scaffolds could take part in hydrogen bonds, donor‐acceptor interactions with various enzymes and receptors [6] . Currently, various life‐saving drugs contain isoxazoles and isoxazolines moieties (Figure 1A) [7] and 5‐hydroxy‐2‐isoxazolines have been utilized as a versatile synthon possibly because it can be easily transformed into various functional groups like isoxazoles, β ‐enaminones, 1,3‐diketones, γ ‐amino alcohols, and N ‐aryl‐ β ‐lactams, etc [8–10] . Isoxazoles are also extensively used as 1,3‐dicarbonyl equivalents in natural product synthesis [11] .…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of highly functionalized cyclopentane derivatives gained considerable attention in medicinal chemistry, as a result of their various biological activities. [15][16][17][18][19][20][21][22][23][24] Some isoxazoline derivatives were earlier synthesized starting from various cyclic -amino acids by applying regio-and stereoselective 1,3-dipolar cycloaddition of nitrile oxide. [24][25][26][27][28][29] Moreover, cyclic -amino This document was downloaded for personal use only.…”
Section: Introductionmentioning
confidence: 99%